Fast Photo-Realistic Rendering of Trees in Daylight - Qin, Xueying; Nakamae, Eihachiro; Tadamura, Katsumi; Nagai, Yasuo (Computer graphics forum, 2003)
We propose a fast approach for photo‐realistic rendering of trees under various kinds of daylight, which is particularlyuseful for the environmental assessment of landscapes. In our approach the 3D tree models are transformedto a quasi‐3D tree database registering geometrical and shading information of tree surfaces, i.e. their normalvectors, relative depth, and shadowing of direct sunlight and skylight, by using a combination of 2D buffers.Thus the rendering speed of quasi‐3D trees depends on their display sizes only, regardless of the complexity oftheir original 3D tree models. By utilizing a two‐step shadowing algorithm, our proposed method can create highquality forest scenes illuminated by both sunlight and skylight at a low cost. It can generate both umbrae andpenumbrae on a tree cast by other trees and any other objects such as buildings or clouds. Transparency, specularreflection and inter‐reflection of leaves, which influence the delicate shading effects of trees, can also be simulatedwith verisimilitude. Categories and Subject Descriptors (according to ACM CCS): I.3.7 [Computer Graphics]: Three dimensional Graphics and Realism